Inquiry-Based Digital Physics Learning Integrated with Glocal Wisdom for Education for Sustainable Development - Hanan Zaki Alhusni; Riski Ramadani; Binar Kurnia Prahani; Titin Sunarti; Madlazim Madlazim (Journal of Innovative Technology and Sustainability Education, 2025)
Objective: This study aims to analyse the integration of inquiry-based learning, digital technology, Education for Sustainable Development (ESD), and glocal wisdom in physics education through a systematic literature review. The goal is to map trends, patterns, and research gaps connecting these dimensions to improve conceptual understanding, critical thinking, and sustainability-oriented learning. Method: A Systematic Literature Review (SLR) was conducted based on PRISMA 2020 guidelines. Data were collected from Scopus, Web of Science, SpringerLink, and ScienceDirect, covering studies published from 2015 to 2025. Of the 1,428 identified articles, 54 met the inclusion criteria. Data were analysed using thematic analysis with NVivo 14 to identify key research themes and directions. Results: Four major themes emerged: (1) effectiveness of inquiry-based digital learning in enhancing reasoning and conceptual mastery; (2) integration of digitalisation and ESD to foster ecological literacy; (3) application of glocal wisdom as a cultural context to enhance relevance and inclusivity; and (4) ethical and equity challenges in technology implementation. These findings indicate a paradigm shift from content-based physics learning to contextual and sustainability-driven education. Novelty: This study offers an integrative synthesis that combines inquiry, digitalisation, ESD, and cultural wisdom within a single framework. Its novelty lies in presenting a holistic model of physics education that promotes scientific literacy, environmental awareness, and cultural identity toward sustainable learning.